Bacteria meets influenza A virus: A bioluminescence mouse model of Escherichia coli O157:H7 following influenza A virus/Puerto Rico/8/34 (H1N1) strain infection. Issue 7 (July 2018) - Wang, Zhongyi; Chi, Hang; Wang, Xiwen; Li, Wenliang; Li, Zhiping; Li, Jiaming; Fu, Yingying; Lu, Bing; Xia, Zhiping; Qian, Jun; Liu, Linna
Objective: To develop a bioluminescence-labelled bacterial infection model to monitor the colonization and clearance process of Escherichia coli O157:H7 in the lungs of mice following influenza A virus/Puerto Rico/8/34 (H1N1) strain (IAV/PR8) infection. Methods: BALB/c mice were administered IAV/PR8 or 0.01 M phosphate-buffered saline (PBS; pH 7.4) intranasally 4 days prior to intranasal administration of 1 × 10 7 colony-forming units (CFU) of E. coli O157:H7-lux. Whole-body bioluminescent signals were monitored at 10 min, 4 h, 8 h, 12 h, 16 h and 24 h post-bacterial infection. Lung bioluminescent signals and bacterial load (CFU/g) were monitored at 4 h, 8 h, 12 h, 16 h and 24 h post-bacterial infection. Results: Prior IAV/PR8 infection of mice resulted in a higher level of bacterial colonization and a lower rate of bacterial clearance from the lungs compared with mice treated with PBS. There were also consistent findings between the bioluminescence imaging and the CFU measurements in terms of identifying bacterial colonization and monitoring the clearance dynamics of E. coli O157:H7-lux in mouse lungs. Conclusion: This novel bioluminescence-labelled bacterial infection model rapidly detected bacterial colonization of the lungs and monitored the clearance dynamics of E. coli O157:H7-lux following IAV/PR8 infection.